Functional characterization of calcium sensing receptor polymorphisms and absence of association with indices of calcium homeostasis and bone mineral density. - Harding, B; Curley, A; Hannan, F; Christie, P; Bowl, MR; Turner, J; Barber, M; Gillham-Nasenya, I; Hampson, G; Spector, T; Thakker, R (2006)
OBJECTIVES: Associations between calcium-sensing receptor (CaSR) polymorphisms and serum calcium, PTH and bone mineral density (BMD) have been reported by six studies. However, three other studies have failed to detect such associations. We therefore further investigated three CaSR coding region polymorphisms (Ala986Ser, Arg990Gly and Gln1011Glu) for associations with indices of calcium homeostasis and BMD and for alterations in receptor function. PATIENTS AND DESIGN: One hundred and ten adult, Caucasian, female, dizygotic twin pairs were investigated for associations between the three CaSR polymorphisms and serum calcium, albumin, PTH, 25-hydroxyvitamin D(3) (25OHD(3)), 1,25-dihydroxyvitamin D(3)[1,25(OH)(2)D(3)], urinary calcium excretion and BMD. Each polymorphic CaSR was also transfected into HEK293 cells and functionally evaluated. RESULTS: There was a lack of association between each of these three CaSR polymorphisms and serum calcium corrected for albumin, PTH, 25OHD(3), 1,25(OH)(2)D(3), urinary calcium excretion or BMD at the hip, forearm and lumbar spine. These findings were supported by a lack of functional differences in the dose-response curves of the CaSR variants, with the EC(50) values (mean +/- SEM) of the wild-type (Ala986/Arg990/Gln1011), Ser986, Gly990 and Glu1011 CaSR variants being 2.74 +/- 0.29 mm, 3.09 +/- 0.34 mm (P > 0.4), 2.99 +/- 0.23 mm (P > 0.4) and 2.96 +/- 0.30 mm (P > 0.5), respectively. CONCLUSIONS: Our study, which was sufficiently powered to detect effects that would explain up to 5%, but not less than 1%, of the variance has revealed that the three CaSR polymorphisms of the coding region have no major influence on indices of calcium homeostasis in this female population, and that they do not alter receptor function.